STRATEGI KOMISI PEMILIHAN UMUM PROVINSI RIAU UNTUK MENINGKATKAN PARTISIPASI PEMILIH PEMULA PADA PEMILIHAN UMUM SERENTAK 2024 - Rosana Febryanti Putri; Data Wardana (SULTAN ADAM: Jurnal Hukum dan Sosial, 2024)
This research aims to find out the strategies the General Election Commission has taken to increase the participation of novice voters and the obstacle of the General Election Commission has faced to provide information to novice voters to not be abstain in the 2024 general election in Riau Province. This research is using a descriptive method with a qualitative approach. The results of this study shown that the General Election Commission of Riau Provinceo carries out its strategy by socializing to novice voters, especially among high schools and University’s Students held by the General Election Commission of Riau Province and conduct voting simulation directly by students so that they know the flow of voting steps. The General Election Commission of Riau Provinse also provides socializatiob through their social media so the public can reach the latest information about general election in 2024.